Review of patient‐reported outcome measures for use in myotonic dystrophy type 1 patients. Issue 1 (1st March 2017) - Symonds, Tara; Randall, Jason A.; Campbell, Patrick
ABSTRACT: Introduction: The heterogeneity of symptoms experienced by myotonic dystrophy type 1 (DM1) patients means patient‐reported outcome (PRO) assessments are uniquely suited to address this through questionnaires. Methods: A structured literature review of PRO measures used in DM1 populations, comparing psychometric data from this population was undertaken. Results: One health status measure, 3 activities of daily living (ADL) scales, 3 health‐related quality of life (HRQOL) assessments, and 5 sleep and fatigue measures have validity and reliability information from DM1 populations. The Myotonic Dystrophy Health Index and DM1 Activity and Participation Scale (DM1‐Activ) have the strongest validity and reliability evidence. The DM1‐Activ c has been published recently and builds on the DM1‐Activ by adding more relevant items. Conclusions: The PRO instruments we identified have varying psychometric evidence in DM1 populations; all require further testing to be confident of their ability to make accurate and valid measurements of symptoms, HRQOL, and ADL in a DM1 population. Muscle Nerve 56 : 86–92, 2017.